The Artificial Leaf: Recent Progress and Remaining Challenges - Symes, Mark D. (UI Scholars Hub, 2016)
The prospect of a device that uses solar energy to split water into H2 and O2 is highly attractive in terms of producing hydrogen as a carbon-neutral fuel. In this mini review, key research milestones that have been reached in this field over the last two decades will be discussed, with special focus on devices that use earth-abundant materials. Finally, the remaining challenges in the development of such “artificial leaves” will be highlighted.